Catalytic Enantioselective Synthesis of N, Cα, Cα‐Trisubstituted α‐Amino Acid Derivatives Using 1H‐Imidazol‐4(5H)‐ones as Key Templates1. Issue 23 (23rd April 2015) - Etxabe, Julen; Izquierdo, Joseba; Landa, Aitor; Oiarbide, Mikel; Palomo, Claudio
Abstract: 1 H ‐Imidazol‐4(5 H )‐ones are introduced as novel nucleophilic α‐amino acid equivalents in asymmetric synthesis. These compounds not only allow highly efficient construction of tetrasubstituted stereogenic centers, but unlike hitherto known templates, provide direct access to N‐substituted (alkyl, allyl, aryl) α‐amino acid derivatives. Abstract : A BB method : 1 H ‐imidazol‐4(5 H )‐ones serve as effective and easily available α‐amino acid surrogates for the catalytic and highly diastereo‐ and enantioselective direct construction of N‐substituted quaternary α‐amino acid derivatives. The reaction is catalyzed by a Brønsted base (BB) and proceeds with different Michael acceptors. EWG=electron‐withdrawing group.